Microbial consortium can enhance plant growth, control leaf miners and parasitic root nematodes in tomato crops grown in Mediterranean greenhouse - Rizzo, Giulio Flavio; Ciccarello, Luca; Arena, Donata; Catara, Vittoria; Siscaro, Gaetano; Gfeller, Valentin; Messmer, Monika M.; Branca, Ferdinando (Frontiers in Horticulture, 2026)
IntroductionMicrobial inoculants based on plant growth-promoting microbes offer a promising alternative to chemical inputs, enhancing plant growth, crop yield, and stress resilience without adverse environmental effects.MethodsA commercial microbial consortium (Bacillus spp., Pseudomonas spp., Streptomyces spp., Trichoderma spp., Glomus spp.) was evaluated in a cold greenhouse in Sicily (Italy), certified for organic methods. The consortium was applied by fertigation to five tomato cultivars, including one commercial and four Sicilian landraces. The greenhouse was naturally infested with the tomato leaf miner Phthorimaea absoluta, which affected plant growth and yield. Results and discussionDespite the considerable infestation, plants treated by the above-cited microbial consortium showed enhanced growth and yield compared to the control plants. Furthermore, root galls caused by nematodes (Meloidogyne spp.) were observed. Significant differences were observed among the genotype and the treatment. Microbial DNA was extracted from tomato roots and analyzed using amplicon sequencing to characterize the root-associated bacterial, fungal, and nematode communities. Alpha diversity indices were largely unaffected for bacteria. In contrast, the genotype and the soil treatment by the microbial consortium affected the alpha diversity indices for fungi and nematodes. Beta diversity analysis revealed significant differences in microbiota community composition between plants grown in treated and untreated soils for both datasets analyzed. Furthermore, we found several Operational taxonomic units associated with the soil treatment by the microbial consortium utilized. Finally, the results demonstrated that the microbial consortium utilized alleviated the damage symptoms due to biotic stresses (P. absoluta and Meloidogyne spp.). Furthermore, the treatment significantly affected the microbial community of the tomato roots depending on the cultivars used.